Facilitating experience capitalization: A guidebook - Eggens, Laura; Chavez-Tafur, Jorge (Technical Centre for Agricultural and Rural Cooperation, 2019)
Since April 2016, CTA implemented the “Capitalizing on Experiences for Greater Impact in Rural Development” project – working together with FAO and IICA, and with the financial support of IFAD. During these three years, this project worked with many organizations in different parts of the world. Its purpose was to empower these organizations with the tools and the skills needed to identify practices which can be brought to scale, to describe and analyze them in detail, and to share the lessons they teach. More specifically, this project aimed to facilitate the adoption of an experience capitalization process in rural development initiatives. This guidebook is meant to help facilitators. It builds on the many interesting resources which are already available, but it builds more specifically on the experience accumulated by the project, and on the lessons and insights drawn by all those who were involved in it – both as facilitators and as participants. It is their work which has shown what works and what can be presented as a recommendation that others can follow and adapt.